PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA KARYAWAN PADA PT. SURYA MUSTIKA NUSANTARA AMC – MALANG - Mokh. Idham Kholid; Woro Utari (Jurnal Manajerial Bisnis, 2023)
The purpose of this research is to analyze the influence of leadership style and work environment on performance both directly and indirectly through employee job satisfaction. This research is a explanatory research with a quantitative approach. The population in this research were all employees of PT. Surya Mustika Nusantara AMC - Malang totaling 127 people. The number of samples taken in this research were 56 employees. The results of the research and data analysis showed that job satisfaction and leadership style got very good index values, while work performance and environment got good index values. Leadership style has a direct positive effect on job satisfaction, work environment has a direct positive effect on job satisfaction, leadership style has a direct positive effect on performance, work environment has a direct positive effect on performance, job satisfaction has a direct positive effect on performance, influential leadership style indirectly positive for performance through job satisfaction, and the work environment has an indirect positive effect on performance through job satisfaction.